Location, location, location [location-based games]. - Kushner, D. (IEEE spectrum)
This paper discusses the latest development in the gaming industry, called mobile gaming. One of the first so-called location-based games is called Raygun, from the Washington-based game developer, GloVentures LLC. Raygun is played with a mobile device such as a cellphone or a PDA, and uses GPS technology to transform the real world into a virtual arena. Plans are underway to develop more narrative-based games that would allow players to explore a fantasy world and solve intricate puzzles.